2017
DOI: 10.1590/1806-93042017000200004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with alcohol consumption during pregnancy

Abstract: 045g±71.0 vs 3,192g±19.2; p=0.040).Conclusions: identifying and characterizing women who are more susceptible to alcohol consumption during pregnancy can contribute to developing more effective public health intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
1
13
0
3
Order By: Relevance
“…Unexpectedly, alcohol use during pregnancy was observed to reduce the risk of perinatal death before imputation of missing values and after imputation using the GEE binomial regression model. We did not find a significant association in the GEE with a log-linear regression model, which agrees with other studies [47]. However, maternal alcohol consumption during pregnancy has been associated with a decreased risk of being small for gestational age (below 10 th percentile related to gestational age and sex) and that of preterm birth [48].…”
Section: Plos Onesupporting
confidence: 91%
“…Unexpectedly, alcohol use during pregnancy was observed to reduce the risk of perinatal death before imputation of missing values and after imputation using the GEE binomial regression model. We did not find a significant association in the GEE with a log-linear regression model, which agrees with other studies [47]. However, maternal alcohol consumption during pregnancy has been associated with a decreased risk of being small for gestational age (below 10 th percentile related to gestational age and sex) and that of preterm birth [48].…”
Section: Plos Onesupporting
confidence: 91%
“…The group of participants, defined purposively, consisted of 14 adult women, who were pregnant during the second half of 2015 and the first half of 2016. These women participated in a previous study developed by our group [10] and were identified as risk-drinkers during pregnancy by the Brazilian validated revised T-ACE screening tool [13, 36]. The T-ACE screening tool is a questionnaire consisting of four main questions; a score is assigned for each one of these questions and the maximum value of the questionnaire is equal to 5.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 59 T-ACE positive women were selected as possible participants. Women were contacted by telephone and invited to participate in the research, referred to primarily as a study about pregnancy habits and alcohol consumption to which they were invited to due to alcohol consumption identification in our previous research [10]. Not all women answered the phone call; therefore, researchers were only able to contact 21 out of the 59 women by the telephone numbers indicated in our previous study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A consequência mais grave desse consumo é designada como Síndrome Alcoólica Fetal (SAF). (1) Contudo algumas crianças podem apresentar um fenótipo específico com a exposição ao etanol intra útero, mas sem se enquadrar necessariamente como SAF, sendo referidas pelo termo "Transtornos do Espectro Alcoólico Fetal (TEAF)", do inglês Fetal Alcohol Spectrum Disorders (FASD) (2)(3) .…”
Section: Abstract: Fetal Alcohol Spectrum Disorders Eye Diseases Reunclassified